Blended Learning Strategy as A Means of Optimizing Learning - Mastur Mastur (Universitas Pahlawan Tuanku Tambusai, 2023)
Covid-19 has affected various sectors, one of which is education. The process of changing the learning model from face-to-face to online and offline, as well as combinations that can have an impact. Students complain about the lack of teacher interaction, so they lose motivation to learn, which can reduce learning outcomes, so an alternative solution to the problem is needed. Researchers researched applying the blended learning model to students to optimize the learning process in the Covid 19 and New Normal pandemic era. The method used in this study is an analytical method with a literature review that is descriptive through various literature studies in strengthening the analysis, which is supported by multiple sources. The study results showed that blended learning using online e-learning media Edmodo, LMS Moodle, and Google Classroom could optimize education and foster students' critical thinking skills; however, Google Classroom is more recommended.